Harnessing a catalytic lysine residue for the one-step preparation of homogeneous antibody-drug conjugates. Issue 1 (December 2017) - Nanna, Alex; Li, Xiuling; Walseng, Even; Pedzisa, Lee; Goydel, Rebecca; Hymel, David; Burke Jr., Terrence; Roush, William; Rader, Christoph
Abstract Current strategies to produce homogeneous antibody-drug conjugates (ADCs) rely on mutations or inefficient conjugation chemistries. Here we present a strategy to produce site-specific ADCs using a highly reactive natural buried lysine embedded in a dual variable domain (DVD) format. This approach is mutation free and drug conjugation proceeds rapidly at neutral pH in a single step without removing any charges. The conjugation chemistry is highly robust, enabling the use of crude DVD for ADC preparation. In addition, this strategy affords the ability to precisely monitor the efficiency of drug conjugation with a catalytic assay. ADCs targeting HER2 were prepared and demonstrated to be highly potent and specific in vitro and in vivo. Furthermore, the modular DVD platform was used to prepare potent and specific ADCs targeting CD138 and CD79B, two clinically established targets overexpressed in multiple myeloma and non-Hodgkin lymphoma, respectively. Current strategies for producing antibody-drug conjugates often rely on inefficient conjugation chemistry or on generating mutations in the antibody sequence. Here the authors demonstrate a mutation-free, single-step conjugation platform utilizing a buried lysine residue.